A kind of crack-resistant and anti-seepage concrete and its preparation method and application
Through the combination of modified manganese slag, modified gel powder and modified composite fiber, the problem that concrete in the prior art is difficult to take into account both mechanical strength, anti-seepage and crack resistance, and high strength and excellent anti-seepage resistance are achieved 裂性能的抗裂防渗混凝土,适用于高要求工程项目。
Patent Information
- Application Number
- CN202411325222.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The prior art is difficult to take into account the mechanical strength, anti-seepage and crack resistance of concrete, and is not sufficiently performed especially in high-demand engineering projects such as dams and reservoirs.
Using modified manganese slag, modified gel powder and modified composite fiber as additives, a crack-resistant and anti-seepage concrete is formed through specific immersion, sintering and low-temperature plasma treatment methods, combining cement, coarse aggregates and fine aggregates. , optimize the ratio and process flow.
Concrete with a compressive strength of about 80Mpa and a flexural strength of more than 21Mpa has been achieved, and its anti-seepage and cracking resistance are excellent, and its cracking area is less than 40mm2/m2. It is suitable for engineering projects such as dams and reservoirs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new materials, relates to the technical field of advanced concrete materials, and specifically relates to a crack-resistant and seepage-proof concrete and a preparation method and application thereof. Background Art
[0002] At present, in order to meet the performance requirements of anti-seepage and anti-cracking, the main additives used in cement concrete include inorganic waterproof materials, expansion agents, shrinkage reducers, fibers, mineral admixtures, etc. In general, those skilled in the art usually consider adding only one of the above additives, but it is often impossible to take into account all the properties of concrete, especially mechanical strength, anti-seepage performance and anti-cracking performance, which makes the resulting concrete difficult to use in projects with higher use requirements, such as dams or reservoirs.
[0003] Chinese patent CN 114790097 B provides an anti-seepage concrete for reservoir dams and a preparation method thereof, which combines the advantages of magnetic graphene, fiber and mineral admixtures to obtain a mixed additive and a concrete with relatively balanced mechanical strength and anti-seepage performance. However, the patent does not examine the crack resistance of the obtained concrete, and the mechanical strength of the obtained concrete is insufficient, inferior to the common concrete in the prior art, and has low practical application value.
[0004] Chinese patent CN 114133184 B provides a crack-resistant and anti-seepage ready-mixed concrete and its preparation process. On the basis of adding slag powder and corn slag powder, the copolymer is modified and combined with other compounds. On the basis of adding fiber and nano boron silicon, a crack-resistant and anti-seepage concrete is obtained. The concrete has high compressive strength and good crack resistance. The obtained compressive strength is close to 70Mpa, which is better than conventional concrete. The crack area of the obtained concrete is less than 100mm 2 / m 2 .
[0005] However, as the paper "Composition Design and Performance Research of Anti-seepage and Anti-cracking Composite Admixtures" [1] As discussed in the introduction, in the prior art, when preparing anti-seepage and anti-cracking concrete, the technicians in this field have not yet figured out the rules on how to modify and combine different additives to produce synergistic effects and improve the relevant properties of concrete. This makes it a challenging research task to develop a concrete with both high mechanical strength and good anti-seepage and anti-cracking properties. Summary of the invention
[0006] The present invention aims to overcome the defects of the prior art, and to overcome the shortcomings of the prior art that it is difficult to take into account both anti-seepage and anti-cracking properties, as well as difficulty in obtaining higher strength when preparing concrete, thereby providing a concrete that can better take into account both anti-seepage and anti-cracking properties, and the concrete also has higher mechanical strength.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A crack-resistant and anti-seepage concrete, wherein the raw materials of the crack-resistant and anti-seepage concrete include cement, coarse aggregate, fine aggregate and additives;
[0009] The additive comprises, by weight, 100 parts of modified manganese slag, 2 to 5 parts of modified gel powder and 6 to 10 parts of modified composite fiber;
[0010] The modified manganese slag is obtained by soaking electrolytic manganese slag, cordierite and fly ash in alkali solution and hydrogen peroxide in a weight ratio of 10:2 to 4:5, and then sintering and grinding into powder;
[0011] The modified gel powder is obtained by adding nano cerium oxide and nano yttrium oxide to a sodium alginate aqueous solution at a weight ratio of 3 to 5:5, adding calcium chloride solution to cross-link into gel after mixing, and then freeze-drying and grinding into powder;
[0012] The modified composite fiber is obtained by subjecting polyester fiber and cellulose fiber to low-temperature plasma treatment using oxygen as a modifying gas.
[0013] Preferably, the additive consists of 100 parts by weight of modified manganese slag, 4 parts by weight of modified gel powder and 8 parts by weight of modified composite fiber.
[0014] Preferably, the modified manganese slag is obtained by soaking electrolytic manganese slag, cordierite and fly ash in alkali solution and hydrogen peroxide in a weight ratio of 10:3:5, and then sintering and grinding them into powder.
[0015] Preferably, when the alkali solution and hydrogen peroxide soaking treatment is carried out, 90 parts of a solid phase consisting of electrolytic manganese slag, cordierite and fly ash, 5 parts of alkali solution and 5 parts of hydrogen peroxide are taken in parts by weight, added to 300 parts of deionized water, and reacted at 60°C for 5 hours; wherein the alkali solution is a 30% w / w sodium hydroxide solution, and the hydrogen peroxide is a 30% v / v hydrogen peroxide solution.
[0016] Preferably, during the sintering, the sintering is performed at 1050-1100° C. for 90-95 minutes.
[0017] Preferably, when preparing the modified gel powder, the weight ratio of nano-cerium oxide to nano-yttrium oxide is 4:5.
[0018] Preferably, when preparing the modified gel powder, nano cerium oxide, nano yttrium oxide and sodium alginate are prepared in a weight ratio of 4:5:10, and then dissolved in deionized water to form a sodium alginate weight content of 2%; during cross-linking, the calcium chloride solution is a 1% w / w calcium chloride aqueous solution.
[0019] Preferably, when preparing the modified composite fiber, the weight ratio of polyester fiber to cellulose fiber is 1:1, and when performing low-temperature plasma treatment, the voltage is 45V, the current is 2A, and the distance between the two electrodes is 6 mm.
[0020] Preferably, the cement is P.O42.5 silicate cement, the coarse aggregate is crushed stone, and the fine aggregate is fine sand; the additive accounts for 6-8% of the weight of the concrete raw materials.
[0021] Another object of the present invention is to provide a method for preparing the above concrete, which comprises mixing the raw materials of the above crack-resistant and seepage-proof concrete, adding water, stirring and then pouring.
[0022] Another object of the present invention is to provide the application of the above concrete in the preparation of dam and reservoir buildings.
[0023] Beneficial effects of the present invention:
[0024] The concrete obtained by the present invention has excellent performance, with a compressive strength of about 80Mpa and a flexural strength of more than 21Mpa; the anti-seepage and crack resistance of the obtained concrete are very excellent, and the crack area is less than 40mm 2 / m 2 The present invention has good industrial application value and can be applied in engineering projects such as dams and reservoirs. DETAILED DESCRIPTION
[0025] In order to better understand the essence of the present invention, the technical content of the present invention is described in detail below with reference to examples, but the content of the present invention is not limited thereto and cannot be understood as limiting the patent scope of the present invention.
[0026] The raw materials involved in the examples of the present invention or the comparative examples are as follows:
[0027] Fly ash: According to GB / T 1596-2017, Class F primary fly ash, Emeishan Taixin Environmental Protection Technology Co., Ltd.;
[0028] Cordierite: 200-325 mesh, Kunjian Mineral Products Processing Plant, Lingshou County;
[0029] Sepiolite: Lingshou County Zekai Mineral Products Co., Ltd.
[0030] Manganese slag: electrolytic manganese slag from Sanhe Manganese Industry in Tongren, Guizhou, with an average particle size of 11μm. Among the main components, the content of Fe2O3 is 5.6%, the content of MnO is 2.2%, the content of SiO2 is 36.3%, the content of Al2O3 is 10.6%, and the content of CaO is 9.4%;
[0031] Polyester fiber: Laiwu Xingtai Engineering Materials Co., Ltd.;
[0032] Cellulose fiber: Taian Yilin New Materials Co., Ltd.;
[0033] Polypropylene fiber: Chengdu Aoneng Tianwei Building Materials Co., Ltd.;
[0034] Nano-cerium oxide: Sichuan Wonaix New Material Technology Co., Ltd.;
[0035] Nano-yttrium oxide: Sichuan Quanyue Metal Materials Co., Ltd.;
[0036] Sodium hydroxide solution: 30% w / w, self-prepared;
[0037] Hydrogen peroxide solution: 30% v / v, self-prepared;
[0038] Crushed stone: Inactive crushed stone, with a particle size of 5~20mm (40%) and a particle size of 20~40mm (60%), and an apparent density of 2700kg / m 3 , water absorption rate 0.6%, locally purchased.
[0039] Fine sand: natural river sand, fineness modulus 2.82, mud content 2.4%, apparent density 2680kg / m 3 , water absorption rate 1.3%, locally purchased.
[0040] Example 1
[0041] 1. Preparation of additives:
[0042] Modified manganese slag: prepare electrolytic manganese slag, cordierite and fly ash in a weight ratio of 10:3:5, mix them thoroughly to obtain a mixture; then mix the above mixture, sodium hydroxide solution, hydrogen peroxide solution and deionized water in a weight ratio of 95:5:5:300; then heat to 60°C for reaction for 5 hours, then cool naturally, take the solid phase and dry the moisture; then place the dried solid phase material in a muffle furnace, sinter at 1100°C for 90 minutes, cool naturally, and grind into powder.
[0043] Modified gel powder: prepare nano cerium oxide, nano yttrium oxide and sodium alginate in a weight ratio of 4:5:10, add sodium alginate into deionized water, slowly add nano cerium oxide and nano yttrium oxide during slow stirring to form a solution with a sodium alginate weight content of 2%; then slowly add 1% w / w calcium chloride aqueous solution to cross-link into gel; after gelation, chop the gel blocks, and then freeze-dry and grind into powder.
[0044] Modified composite fiber: Polyester fiber and cellulose fiber were prepared in a weight ratio of 1:1, and low-temperature plasma treatment was performed with oxygen as the gas atmosphere, a voltage of 45 V, a current of 2 A, and a distance between two electrodes of 6 mm.
[0045] Additives: Mix 100 parts of modified manganese slag, 4 parts of modified gel powder and 8 parts of modified composite fiber by weight.
[0046] 2. Preparation of concrete:
[0047] By weight, take 200 parts of cement, 280 parts of crushed stone, 420 parts of fine sand, 80 parts of water, and 60 parts of additives as the concrete material ratio. First, mix the crushed stone and fine sand evenly, then add cement and continue mixing, and finally add water and additives and mix. Then put it into the mold and vibrate for 30 seconds, then let it stand in a cool place for 1 day, and then put it into a standard curing room for curing to the specified age.
[0048] Example 2
[0049] Modified manganese slag: prepare electrolytic manganese slag, cordierite and fly ash in a weight ratio of 10:2:5, mix them thoroughly to obtain a mixture; then mix the above mixture, sodium hydroxide solution, hydrogen peroxide solution and deionized water in a weight ratio of 95:5:5:300; then heat to 60°C for reaction for 5 hours, then cool naturally, take the solid phase and dry the moisture; then place the dried solid phase material in a muffle furnace, sinter at 1100°C for 90 minutes, and grind it into powder after natural cooling.
[0050] Modified gel powder: prepare nano cerium oxide, nano yttrium oxide and sodium alginate in a weight ratio of 5:5:10, add sodium alginate into deionized water, slowly add nano cerium oxide and nano yttrium oxide during slow stirring to form a solution with a sodium alginate weight content of 2%; then slowly add 1% w / w calcium chloride aqueous solution to cross-link into gel; after gelation, chop the gel blocks, and then freeze-dry and grind into powder.
[0051] Modified composite fiber: Polyester fiber and cellulose fiber were prepared in a weight ratio of 1:1, and low-temperature plasma treatment was performed with oxygen as the gas atmosphere, a voltage of 45 V, a current of 2 A, and a distance between two electrodes of 6 mm.
[0052] Additives: Mix 100 parts of modified manganese slag, 2 parts of modified gel powder and 10 parts of modified composite fiber by weight.
[0053] 2. Preparation of concrete:
[0054] By weight, take 200 parts of cement, 280 parts of crushed stone, 420 parts of fine sand, 80 parts of water, and 60 parts of additives as the concrete material ratio. First, mix the crushed stone and fine sand evenly, then add cement and continue mixing, and finally add water and additives and mix. Then put it into the mold and vibrate for 30 seconds, then let it stand in a cool place for 1 day, and then put it into a standard curing room for curing to the specified age.
[0055] Example 3
[0056] Modified manganese slag: prepare electrolytic manganese slag, cordierite and fly ash in a weight ratio of 10:4:5, mix them thoroughly to obtain a mixture; then mix the above mixture, sodium hydroxide solution, hydrogen peroxide solution and deionized water in a weight ratio of 95:5:5:300; then heat to 60°C for reaction for 5 hours, then cool naturally, take the solid phase and dry the moisture; then place the dried solid phase material in a muffle furnace, sinter at 1050°C for 95 minutes, cool naturally, and grind into powder.
[0057] Modified gel powder: prepare nano cerium oxide, nano yttrium oxide and sodium alginate in a weight ratio of 3:5:10, add sodium alginate into deionized water, slowly add nano cerium oxide and nano yttrium oxide during slow stirring to form a solution with a sodium alginate weight content of 2%; then slowly add 1% w / w calcium chloride aqueous solution to cross-link into gel; after gelation, chop the gel blocks, and then freeze-dry and grind into powder.
[0058] Modified composite fiber: Polyester fiber and cellulose fiber were prepared in a weight ratio of 1:1, and low-temperature plasma treatment was performed with oxygen as the gas atmosphere, a voltage of 45 V, a current of 2 A, and a distance between two electrodes of 6 mm.
[0059] Additives: Mix 100 parts of modified manganese slag, 5 parts of modified gel powder and 6 parts of modified composite fiber by weight.
[0060] 2. Preparation of concrete:
[0061] By weight, take 200 parts of cement, 280 parts of crushed stone, 420 parts of fine sand, 80 parts of water, and 60 parts of additives as the concrete material ratio. First, mix the crushed stone and fine sand evenly, then add cement and continue mixing, and finally add water and additives and mix. Then put it into the mold and vibrate for 30 seconds, then let it stand in a cool place for 1 day, and then put it into a standard curing room for curing to the specified age.
[0062] Comparative Example 1
[0063] When preparing the additive, the modified manganese slag used does not contain cordierite, and the rest is consistent with Example 1.
[0064] The specific scheme of this comparative example is as follows:
[0065] 1. Preparation of additives:
[0066] Modified manganese slag: prepare electrolytic manganese slag and fly ash in a weight ratio of 10:5, mix them thoroughly to obtain a mixture; then mix the above mixture, sodium hydroxide solution, hydrogen peroxide solution and deionized water in a weight ratio of 95:5:300; then heat to 60°C for reaction for 5 hours, then cool naturally, take the solid phase and dry the moisture; then place the dried solid phase material in a muffle furnace, sinter at 1100°C for 90 minutes, cool naturally, and grind into powder.
[0067] Modified gel powder: prepare nano cerium oxide, nano yttrium oxide and sodium alginate in a weight ratio of 4:5:10, add sodium alginate into deionized water, slowly add nano cerium oxide and nano yttrium oxide during slow stirring to form a solution with a sodium alginate weight content of 2%; then slowly add 1% w / w calcium chloride aqueous solution to cross-link into gel; after gelation, chop the gel blocks, and then freeze-dry and grind into powder.
[0068] Modified composite fiber: Polyester fiber and cellulose fiber were prepared in a weight ratio of 1:1, and low-temperature plasma treatment was performed with oxygen as the gas atmosphere, a voltage of 45 V, a current of 2 A, and a distance between two electrodes of 6 mm.
[0069] Additives: Mix 100 parts of modified manganese slag, 4 parts of modified gel powder and 8 parts of modified composite fiber by weight.
[0070] 2. Preparation of concrete:
[0071] By weight, take 200 parts of cement, 280 parts of crushed stone, 420 parts of fine sand, 80 parts of water, and 60 parts of additives as the concrete material ratio. First, mix the crushed stone and fine sand evenly, then add cement and continue mixing, and finally add water and additives and mix. Then put it into the mold and vibrate for 30 seconds, then let it stand in a cool place for 1 day, and then put it into a standard curing room for curing to the specified age.
[0072] Comparative Example 2
[0073] When preparing the additive, the polyester fiber and the cellulose fiber are not subjected to low-temperature plasma treatment, the composite fiber is a mixture of the polyester fiber and the cellulose fiber in a weight ratio of 1:1, and the rest is the same as in Example 1.
[0074] The specific scheme of this comparative example is as follows:
[0075] 1. Preparation of additives:
[0076] Modified manganese slag: prepare electrolytic manganese slag, cordierite and fly ash in a weight ratio of 10:3:5, mix them thoroughly to obtain a mixture; then mix the above mixture, sodium hydroxide solution, hydrogen peroxide solution and deionized water in a weight ratio of 95:5:5:300; then heat to 60°C for reaction for 5 hours, then cool naturally, take the solid phase and dry the moisture; then place the dried solid phase material in a muffle furnace, sinter at 1100°C for 90 minutes, cool naturally, and grind into powder.
[0077] Modified gel powder: prepare nano cerium oxide, nano yttrium oxide and sodium alginate in a weight ratio of 4:5:10, add sodium alginate into deionized water, slowly add nano cerium oxide and nano yttrium oxide during slow stirring to form a solution with a sodium alginate weight content of 2%; then slowly add 1% w / w calcium chloride aqueous solution to cross-link into gel; after gelation, chop the gel blocks, and then freeze-dry and grind into powder.
[0078] Composite fiber: Prepare a mixture of polyester fiber and cellulose fiber in a weight ratio of 1:1.
[0079] Additives: Mix 100 parts of modified manganese slag, 4 parts of modified gel powder and 8 parts of composite fiber by weight.
[0080] 2. Preparation of concrete:
[0081] By weight, take 200 parts of cement, 280 parts of crushed stone, 420 parts of fine sand, 80 parts of water, and 60 parts of additives as the concrete material ratio. First, mix the crushed stone and fine sand evenly, then add cement and continue mixing, and finally add water and additives and mix. Then put it into the mold and vibrate for 30 seconds, then let it stand in a cool place for 1 day, and then put it into a standard curing room for curing to the specified age.
[0082] Comparative Example 3
[0083] When preparing the gel powder, nano cerium oxide and nano yttrium oxide were not added, and only the sodium alginate gel was freeze-dried and ground into powder. The rest was the same as in Example 1.
[0084] The specific scheme of this comparative example is as follows:
[0085] 1. Preparation of additives:
[0086] Modified manganese slag: prepare electrolytic manganese slag, cordierite and fly ash in a weight ratio of 10:3:5, mix them thoroughly to obtain a mixture; then mix the above mixture, sodium hydroxide solution, hydrogen peroxide solution and deionized water in a weight ratio of 95:5:5:300; then heat to 60°C for reaction for 5 hours, then cool naturally, take the solid phase and dry the moisture; then place the dried solid phase material in a muffle furnace, sinter at 1100°C for 90 minutes, cool naturally, and grind into powder.
[0087] Gel powder: Sodium alginate is added into deionized water to form a solution with a sodium alginate weight content of 2%; then 1% w / w calcium chloride aqueous solution is slowly added to cross-link and gel; after gelation, the gel blocks are chopped, freeze-dried, and then ground into powder.
[0088] Modified composite fiber: Polyester fiber and cellulose fiber were prepared in a weight ratio of 1:1, and low-temperature plasma treatment was performed with oxygen as the gas atmosphere, a voltage of 45 V, a current of 2 A, and a distance between two electrodes of 6 mm.
[0089] Additives: Mix 100 parts of modified manganese slag, 4 parts of gel powder and 8 parts of modified composite fiber by weight.
[0090] 2. Preparation of concrete:
[0091] By weight, take 200 parts of cement, 280 parts of crushed stone, 420 parts of fine sand, 80 parts of water, and 60 parts of additives as the concrete material ratio. First, mix the crushed stone and fine sand evenly, then add cement and continue mixing, and finally add water and additives and mix. Then put it into the mold and vibrate for 30 seconds, then let it stand in a cool place for 1 day, and then put it into a standard curing room for curing to the specified age.
[0092] Comparative Example 4
[0093] When preparing the modified gel powder, no nano yttrium oxide was added, and the rest was consistent with Example 1.
[0094] The specific scheme of this comparative example is as follows:
[0095] 1. Preparation of additives:
[0096] Modified manganese slag: prepare electrolytic manganese slag, cordierite and fly ash in a weight ratio of 10:3:5, mix them thoroughly to obtain a mixture; then mix the above mixture, sodium hydroxide solution, hydrogen peroxide solution and deionized water in a weight ratio of 95:5:5:300; then heat to 60°C for reaction for 5 hours, then cool naturally, take the solid phase and dry the moisture; then place the dried solid phase material in a muffle furnace, sinter at 1100°C for 90 minutes, cool naturally, and grind into powder.
[0097] Modified gel powder: prepare nano cerium oxide and sodium alginate at a weight ratio of 4:10, add sodium alginate into deionized water, slowly add nano cerium oxide during slow stirring to form a solution with a sodium alginate weight content of 2%; then slowly add 1% w / w calcium chloride aqueous solution to cross-link into gel; after gelation, chop the gel blocks, freeze-dry them, and grind them into powder.
[0098] Modified composite fiber: Polyester fiber and cellulose fiber were prepared in a weight ratio of 1:1, and low-temperature plasma treatment was performed with oxygen as the gas atmosphere, a voltage of 45 V, a current of 2 A, and a distance between two electrodes of 6 mm.
[0099] Additives: Mix 100 parts of modified manganese slag, 4 parts of modified gel powder and 8 parts of modified composite fiber by weight.
[0100] 2. Preparation of concrete:
[0101] By weight, take 200 parts of cement, 280 parts of crushed stone, 420 parts of fine sand, 80 parts of water, and 60 parts of additives as the concrete material ratio. First, mix the crushed stone and fine sand evenly, then add cement and continue mixing, and finally add water and additives and mix. Then put it into the mold and vibrate for 30 seconds, then let it stand in a cool place for 1 day, and then put it into a standard curing room for curing to the specified age.
[0102] Comparative Example 5
[0103] When preparing the modified composite fiber, the polyester fiber was replaced by the polypropylene fiber, and the rest was the same as in Example 1.
[0104] The specific scheme of this comparative example is as follows:
[0105] 1. Preparation of additives:
[0106] Modified manganese slag: prepare electrolytic manganese slag, cordierite and fly ash in a weight ratio of 10:3:5, mix them thoroughly to obtain a mixture; then mix the above mixture, sodium hydroxide solution, hydrogen peroxide solution and deionized water in a weight ratio of 95:5:5:300; then heat to 60°C for reaction for 5 hours, then cool naturally, take the solid phase and dry the moisture; then place the dried solid phase material in a muffle furnace, sinter at 1100°C for 90 minutes, cool naturally, and grind into powder.
[0107] Modified gel powder: prepare nano cerium oxide, nano yttrium oxide and sodium alginate in a weight ratio of 4:5:10, add sodium alginate into deionized water, slowly add nano cerium oxide and nano yttrium oxide during slow stirring to form a solution with a sodium alginate weight content of 2%; then slowly add 1% w / w calcium chloride aqueous solution to cross-link into gel; after gelation, chop the gel blocks, and then freeze-dry and grind into powder.
[0108] Modified composite fiber: Prepare polypropylene fiber and cellulose fiber in a weight ratio of 1:1, and perform low-temperature plasma treatment with oxygen as the gas atmosphere, a voltage of 45 V, a current of 2 A, and a distance between two electrodes of 6 mm.
[0109] Additives: Mix 100 parts of modified manganese slag, 4 parts of modified gel powder and 8 parts of modified composite fiber by weight.
[0110] 2. Preparation of concrete:
[0111] By weight, take 200 parts of cement, 280 parts of crushed stone, 420 parts of fine sand, 80 parts of water, and 60 parts of additives as the concrete material ratio. First, mix the crushed stone and fine sand evenly, then add cement and continue mixing, and finally add water and additives and mix. Then put it into the mold and vibrate for 30 seconds, then let it stand in a cool place for 1 day, and then put it into a standard curing room for curing to the specified age.
[0112] Comparative Example 6
[0113] When preparing manganese slag, cordierite was replaced by sepiolite, and the rest was consistent with Example 1.
[0114] 1. Preparation of additives:
[0115] Modified manganese slag: prepare electrolytic manganese slag, sepiolite and fly ash in a weight ratio of 10:3:5, mix them thoroughly to obtain a mixture; then mix the above mixture, sodium hydroxide solution, hydrogen peroxide solution and deionized water in a weight ratio of 95:5:5:300; then heat to 60°C for reaction for 5 hours, then cool naturally, take the solid phase and dry the moisture; then place the dried solid phase material in a muffle furnace, sinter at 1100°C for 90 minutes, cool naturally, and grind into powder to obtain the modified manganese slag.
[0116] Modified gel powder: prepare nano cerium oxide, nano yttrium oxide and sodium alginate in a weight ratio of 4:5:10, add sodium alginate into deionized water, slowly add nano cerium oxide and nano yttrium oxide during slow stirring to form a solution with a sodium alginate weight content of 2%; then slowly add 1% w / w calcium chloride aqueous solution to cross-link into gel; after gelation, chop the gel blocks, and then freeze-dry and grind into powder.
[0117] Modified composite fiber: Polyester fiber and cellulose fiber were prepared in a weight ratio of 1:1, and low-temperature plasma treatment was performed with oxygen as the gas atmosphere, a voltage of 45 V, a current of 2 A, and a distance between two electrodes of 6 mm.
[0118] Additives: Mix 100 parts of modified manganese slag, 4 parts of modified gel powder and 8 parts of modified composite fiber by weight.
[0119] 2. Preparation of concrete:
[0120] By weight, take 200 parts of cement, 280 parts of crushed stone, 420 parts of fine sand, 80 parts of water, and 60 parts of additives as the concrete material ratio. First, mix the crushed stone and fine sand evenly, then add cement and continue mixing, and finally add water and additives and mix. Then put it into the mold and vibrate for 30 seconds, then let it stand in a cool place for 1 day, and then put it into a standard curing room for curing to the specified age.
[0121] This experimental example uses GB / T5008-2002 to test the compressive strength and flexural strength of 28-day curing age concrete samples. The water seepage height method in GB / T50082-2009 is used to test the anti-seepage performance of concrete samples. Specifically, the water mark height of the concrete sample is measured after sealing and pressurized to 1.2MPa after 24 hours. GB / T50081-2016 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete" is used to calculate the number of cracks per unit area and the total crack area per unit area measured 24 hours after concrete pouring. In the test, each group of specimens was made into a concrete sample with a length, width and height of 100 mm.
[0122] Table 1
[0123]
[0124] As shown in Table 1, the compressive strength and flexural strength of the concrete obtained in Examples 1-3 of the present invention are relatively high, and compared with the crack-resistant concrete in the prior art, it has strength advantages, for example, "Test on the Effect of Different Anti-cracking Agent Dosages on the Anti-cracking Performance of Hydraulic Concrete" [2] The 28d compressive strength of the concrete obtained was less than 50MPa, and the crack area was higher than 50mm when the anti-cracking agent content reached 10%. 2 / m 2 .
[0125] The present invention uses electrolytic manganese slag as one of the raw materials for concrete, mainly considering that it has been widely studied in this field, such as "Effect of electrolytic manganese slag on compressive strength and pore structure of concrete" [3]The effect of electrolytic manganese slag on the compressive strength of concrete was studied, and it was found that the compressive strength could be increased by up to 82.5% under different addition ratios; for example, "Study on the Effect of Manganese Slag and Slag Compound on the Performance of Cement Concrete" found that by doping electrolytic manganese slag with blast furnace granulated slag, the compressive strength of concrete can reach 52.6Mpa; for example, Chinese patent CN 114605123 B obtained a high-performance concrete with a compressive strength of 160MPa at 90d and a flexural strength of ≥25MPa by compounding electrolytic manganese slag powder, silica fume, limestone powder and calcium sulfate whiskers. In addition to directly using electrolytic manganese slag as an additive, some studies have treated electrolytic manganese slag, such as Chinese patent CN 113603377 B; mixing electrolytic manganese slag with quicklime and spraying a treatment agent to treat it, realizing the reuse of electrolytic manganese slag; for example, "Research on the Mechanical Properties of New Concrete Doped with Electrolytic Manganese Slag (EMR) Sintered Shale Brick Powder" [4] By mixing electrolytic manganese slag, clay and fly ash and then sintering them, the compressive strength and flexural strength of concrete can be slightly improved.
[0126] However, it is not difficult to know that when the existing technology uses electrolytic manganese slag to improve the performance of concrete, although the compressive strength and flexural strength of concrete are improved to varying degrees, the compressive strength and flexural strength of the obtained concrete are relatively low. The compressive strength of 28-day-old concrete is extremely difficult to be higher than 60Mpa, and the flexural strength is extremely difficult to be higher than 20Mpa. More importantly, the relevant research did not consider the problems of anti-seepage and anti-cracking performance.
[0127] The present invention has found through continuous exploration that when modifying electrolytic manganese slag, the electrolytic manganese slag, cordierite and fly ash are mixed, first soaked with alkali solution and hydrogen peroxide, then sintered at high temperature, and combined with other modifiers of the present invention to form additives, the compressive strength of the concrete can reach about 80Mpa, and the flexural strength can reach more than 21Mpa; more importantly, the obtained concrete has excellent anti-seepage and crack resistance, and the crack area is less than 40mm 2 / m 2 , which is superior to the anti-seepage and anti-cracking levels of the prior art additives known to the inventor.
[0128] As shown in Comparative Examples 5 and 6, the use of polyester fiber and cordierite has a great influence on the mechanical strength of the concrete prepared based on the additive of the present invention. However, despite this, the mechanical strength of the concrete obtained in Comparative Examples 5 and 6 is slightly higher than the mechanical strength of the concrete prepared by electrolytic manganese slag in the prior art.
[0129] As shown in Comparative Example 5, the concrete obtained in Comparative Example 5 has the worst impermeability and crack resistance, and the crack area exceeds 200 mm.2 / m 2 The reason may be that the modified composite fiber is not hydrophilic enough, and it is difficult to combine more closely with the modified gel powder and modified manganese slag, resulting in a significant decline in the anti-seepage performance and crack resistance, and a slight impact on the mechanical strength.
[0130] In fact, as additives, whether it is fiber materials, inorganic materials or mineral dopants, there are many studies in the existing technology. Fiber materials can disperse stress concentration, reduce plastic cracks, and inhibit crack development, playing a certain role in anti-seepage and anti-cracking; mineral admixtures can reduce the amount of cement, reduce the early self-drying speed of concrete, and inhibit the shrinkage and cracking of concrete, which to a certain extent promotes the improvement of the concrete's anti-seepage and anti-cracking performance. However, the main problem with the existing technology is that it is difficult to achieve the synergistic effect of various materials, thereby comprehensively improving the performance of concrete. This point is discussed in the master's thesis "Composition Design and Performance Research of Anti-seepage and Anti-cracking Composite Admixtures" [1] The introductory part of the invention has been discussed in detail, and the inventor will not repeat them here.
[0131] In short, combined with the experimental results of Examples 1-3 and Comparative Examples 1-6, the inventors analyzed that the additives of the present invention achieved a synergistic effect, making the concrete more compact and improving the effect of dispersing stress concentration, obtaining excellent anti-seepage and anti-cracking performance, and having high mechanical strength. The mechanism may be that the modified composite fiber has better hydrophilicity through low-temperature plasma treatment, can be more closely combined with the modified gel powder, and at the same time, the fiber enhances the mechanical properties and disperses stress concentration. The addition of cordierite further improves the mechanical properties and further improves the compactness of the concrete together with the nano oxide.
[0132] References:
[0133] [1] Huang Zhen. Composition design and performance research of anti-seepage and anti-cracking composite admixture[D]. Chang'an University, 2013.
[0134] [2] Han Lina. Experiment on the influence of different anti-cracking agent dosage on the anti-cracking performance of hydraulic concrete[J]. Water Conservancy Technical Supervision, 2024, (06): 293-295+300.
[0135] [3] Huang Zhenjiang, Zhao Yu, Hou Junyu, et al. Effect of electrolytic manganese slag on compressive strength and pore structure of concrete[J]. Concrete and Cement Products, 2023, (10): 100-102. DOI: 10.19761 / j.1000-4637.2023.10.100.03.
[0136] [4] Zhang Shengli, Liu Pingwei, Liu Hao, et al. Study on mechanical properties of new type of concrete with sintered shale brick powder mixed with electrolytic manganese slag (EMR)[J]. China Manganese Industry, 2023, 41(03): 15-19. DOI: 10.14101 / j.cnki.issn.1002-4336.2023.03.004.
Claims
1. A crack-resistant and anti-seepage concrete, characterized in that: The raw materials of the crack-resistant and seepage-proof concrete include cement, coarse aggregate, fine aggregate and additives; The additive comprises, by weight, 100 parts of modified manganese slag, 2 to 5 parts of modified gel powder and 6 to 10 parts of modified composite fiber; The preparation method of the modified manganese slag comprises: fully mixing electrolytic manganese slag, cordierite and fly ash according to a weight ratio of 10:2-4:5 to obtain a mixture; then mixing the obtained mixture, sodium hydroxide solution, hydrogen peroxide solution and deionized water according to a weight ratio of 95:5:5:300; then heating to 60°C for reaction for 5 hours; then cooling naturally, taking a solid phase and drying the water; then placing the dried solid phase material in a muffle furnace, sintering at 1050-1100°C for 90-95 minutes, and grinding into powder after natural cooling; wherein the concentration of the sodium hydroxide solution is 30%w / w, and the concentration of the hydrogen peroxide solution is 30%v / v; The modified gel powder is obtained by adding nano cerium oxide and nano yttrium oxide to a sodium alginate aqueous solution at a weight ratio of 3 to 5:5, adding calcium chloride solution to cross-link into gel after mixing, and then freeze-drying and grinding into powder; The modified composite fiber is obtained by subjecting polyester fiber and cellulose fiber to low-temperature plasma treatment using oxygen as a modifying gas.
2. The crack-resistant and anti-seepage concrete according to claim 1, characterized in that: The additive consists of 100 parts of modified manganese slag, 4 parts of modified gel powder and 8 parts of modified composite fiber in parts by weight.
3. The crack-resistant and anti-seepage concrete according to claim 1, characterized in that: The modified manganese slag is obtained by soaking electrolytic manganese slag, cordierite and fly ash in alkali solution and hydrogen peroxide in a weight ratio of 10:3:5, and then sintering and grinding into powder.
4. The crack-resistant and anti-seepage concrete according to claim 1, characterized in that: When preparing the modified gel powder, the weight ratio of nano cerium oxide to nano yttrium oxide is 4:5; when preparing the modified gel powder, nano cerium oxide, nano yttrium oxide and sodium alginate are prepared in a weight ratio of 4:5:10, and then dissolved in deionized water to form a sodium alginate with a weight content of 2%; during cross-linking, the calcium chloride solution is a 1% w / w calcium chloride aqueous solution.
5. The crack-resistant and anti-seepage concrete according to claim 1, characterized in that: When preparing the modified composite fiber, the weight ratio of polyester fiber to cellulose fiber is 1:1, and when performing low-temperature plasma treatment, the voltage is 45V, the current is 2A, and the distance between the two electrodes is 6 mm.
6. The crack-resistant and anti-seepage concrete according to claim 1, characterized in that: The cement is P.O42.5 silicate cement, the coarse aggregate is crushed stone, and the fine aggregate is fine sand; the additive accounts for 6-8% of the weight of the concrete raw materials.
7. A method for preparing crack-resistant and anti-seepage concrete, characterized in that: The preparation method comprises mixing the raw materials of the crack-resistant and seepage-proof concrete according to any one of claims 1 to 6, adding water, stirring and then pouring.
8. Use of the crack-resistant and anti-seepage concrete according to any one of claims 1 to 6 in the preparation of dam and reservoir buildings.
Citation Information
Patent Citations
Cement produced using electrolytic manganese slag and its production method
CN113603377B
A crack-resistant and seepage-proof ready-mixed concrete and its preparation process
CN114133184B
A manganese slag-based ultra-high performance composite cementitious material and concrete material
CN114605123B
A type of impermeable concrete for reservoir dams and its preparation method
CN114790097B
Organic fiber reinforced inorganic geopolymer composite cementitious material and preparation method thereof
CN101570425A
